Characterization of Rock Composing Minerals Using the X-Ray Diffraction Method at the Samaenre-Mallawa Hot Spring, Maros Regency - Yuliana Nengsih; Sahara Sahara; Ayusari Wahyuni (TECHNO: JURNAL PENELITIAN, 2021)
One of the areas in Maros Regency that has geothermal potential is located in Samaenre, Mallawa District, where the hot springs are located a few kilometers from residential areas. This hot water is a source located around the river. Hot springs are springs that are produced as a result of the discharge of groundwater from the earth's crust after being heated geothermal. Research has been carried out that aims to determine the mineral content around hot springs and determine crystal structure around the hot springs by using the X-Ray Diffraction method. Samples were obtained from a depth of 1 meter at points A, B, C, D and E. XRD test results showed that the mineral content was silicon oxide, kaolinite, magnetite, calcium peroxide, Dobassite-2M1a, alpha-SiO2, Calcium Peroxide, Maghemite-Q , Aragonite, Paragonite 2M1, Gehlenite, UTD-1, Silicon Oxide, Pyrophyllite 1A dehydroxylated, Paragonite 3T, and UTD-1. Most of the five samples are silicon oxide minerals. The crystal structures seen are tetragonal CaO2, Fe2O3, (Ca2 (Al0.92 Mg0.08) ((AlO.92), orthorhombic Ca (CO3), Si112 O224, Si O2, hexagonal SiO2, Na Al2 (Al Si3 O10) ( OH)2, monoclinic Al4.5 (Al8.5Si3.2) O10(OH)8, NaAl2 ((AlSi3) O10 (OH)2, triclinic Al4(OH)8(Si4O10), Al4Si2 O22 and cubic Fe3O4.